On Indian ground. - Jacob, Michelle M., 1977-; Johnson, Stephany RunningHawk (On Indian ground ;, 2020)
"On Indian Ground : Northwest is the second of ten regionally focused texts that explores American Indian/Alaska Native/Native Hawaiian education in depth. The text is designed to be used by educators of Native youth and emphasizes best practices found throughout the region. Previous texts on American Indian education make wide-ranging general assumptions that all American Indians are alike. This series promotes specific interventions and relies on Native ways of knowing to highlight place-based educational practices. On Indian Ground: Northwest looks at the history of Indian education across the Pacific Northwest region. Authors also analyze education policy and Tribal education departments to highlight early childhood education, gifted and talented educational practice, parental involvement, language revitalization, counseling, and research. These chapters expose cross-cutting themes of sustainability, historical bias, economic development, health and wellness and cultural competence"--